2004
DOI: 10.1002/pssb.200301923
|View full text |Cite
|
Sign up to set email alerts
|

Ionic disorder and Yaffet–Kittel angle in nanoparticles of ZnFe2O4 prepared by sol‐gel method

Abstract: ZnFe 2 O 4 nanoparticles have been prepared by sol-gel methods. Mössbauer spectra from 4.2 K to RT showed their magnetic ordering took place at much higher temperature than that of bulk zinc ferrite. Mössbauer measurements that cover the temperature range 4.2 K to room temperature were acquired in zero field and an applied magnetic field of 5 T. The large increase of T N for nanoparticles can be attributed mainly to the redistribution of Fe and Zn cations on the A and B sites. Nanoparticles with smaller size h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 7 publications
4
15
0
Order By: Relevance
“…The obtained results are in close agreement with the studies reported earlier for spinel ferrites [14,15]. The center shift results from the electrostatic interaction between the charge distribution of the nucleus and s-electrons with finite probability being found in the region of the nucleus.…”
Section: Mössbauer Analysissupporting
confidence: 94%
“…The obtained results are in close agreement with the studies reported earlier for spinel ferrites [14,15]. The center shift results from the electrostatic interaction between the charge distribution of the nucleus and s-electrons with finite probability being found in the region of the nucleus.…”
Section: Mössbauer Analysissupporting
confidence: 94%
“…All reagents were of analytical grade and used as received without further purification. ZnFe 2 O 4 tubes were synthesized by pyrolysis of PVA-assisted Zn/Fe nitrate gels [16] within the AAO membrane. The typical synthetic process was similar to our previously reported work [12] except that the final calcination temperature was increased from 380 to 450 • C and the sol-precursor concentration was chosen to be 0.15, 0.25 and 0.40 M, respectively.…”
Section: Sample Preparation and Characterizationmentioning
confidence: 99%
“…Several methods such as ball milling [11], sol-gel [12], coprecipitation [13], hydrothermal [14] auto-combustion route [15] and ultrasonic cavitation [16] have been used to synthesize and investigate the magnetic properties of zinc ferrite nanoparticles. However, the coprecipitation is a simple technique to synthesize the ferrite nanoparticles at low temperatures and often without calcination at high temperatures.…”
Section: Introductionmentioning
confidence: 99%